Stem cells: Boon to dentistry and medicine - P S Shilpa; Rachna Kaul; Nishat Sultana; Suraksha Bhat (Wolters Kluwer Medknow Publications, 2013)
Stem cell research has received considerable attention since the discovery that adult stem cells have the capacity to form many different tissue types. Stem cells are a booming field for the research and have been extensively studied in the field of medicine, as well as dentistry. Their application in oncology has been a boon to many of the patients. Dental stem cells have been novel approach to treat diseases like periodontitis, dental caries and many more. Their potential uses in dentistry have provided a new generation of treatments for dental diseases and stem cells have become the focus in dental research. This review highlights about the biology, sources and potential applications of stem cells in dentistry with emphasis on a dentist's role in enabling both medical and dental applications using stem cells from teeth.